(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
This paper summarizes the ongoing researches about the effect of recycled glass powder and the recycled aggregates on conventional concrete Practice. Many studies on using the recycled powdered glass and the recycled aggregates in conventional concrete practice that have been carried out earlier were studied, and their effects on the conventional concrete were also analyzed. In this paper we will analyze the individual effects by these each replacements and then I will combine both the materials in concrete and will analyze the result of that concrete. Glass mainly consists of silica. Utilising the powdered glass waste as fractional replacement could be proven an efficient step for the development of sustainable infrastructure systems. When the recycled waste glass is grinded into the powdered form with micro size particles, it exhibits pozzolanic reactions with the hydrates of cement, resulting in the formation of secondary C-S-H products. Similarly the use of recycled concrete as aggregate would also result into the development of sustainable infrastructure systems. Similarly possibility of utilization of recycled concrete as aggregate has been concluded to have positive impact on the fresh concrete production.